Imitation of snack food intake among normal-weight and overweight children - Bevelander, Kirsten E.; Lichtwarck-Aschoff, Anna; Anschütz, Doeschka J.; Hermans, Roel C.; Engels, Rutger C. (Frontiers in Psychology, 2013)
This study investigated whether social modeling of palatable food intake might partially be explained by the direct imitation of a peer reaching for snack food and, further, assessed the role of the children’s own weight status on their likelihood of imitation during the social interaction. Real-time observations during a 10-minute play situation in which 68 participants (27.9% overweight) interacted with normal-weight confederates (instructed peers) were conducted. Children’s imitated and non-imitated responses to the confederate’s food picking movements were compared using a paired sample t-test. In addition, the pattern of likelihood of imitation was tested using multilevel proportional hazard models in a survival analysis framework. Children were more likely to eat after observing a peer reaching for snack food than without such a cue (t(67) = 5.69, P < .0001). Moreover, findings suggest that children may display different imitation responses during a social interaction based on their weight status (HR = 2.6, P = .03, 95% CI =1.09 – 6.20). Overweight children were almost twice as likely to imitate, whereas normal-weight children had a smaller chance to imitate at the end of the interaction. Further, the mean difference in the likelihood of imitation suggest that overweight children might be less likely to imitate in the beginning of the interaction than normal-weight children. The findings provide preliminary evidence that children’s imitation food picking movements may partly contribute to social modeling effects on palatable food intake. That is, a peer reaching for food is likely to trigger children’s snack intake. However, the influence of others on food intake is a complex process that might be explained by different theoretical perspectives.